Thalamic deep brain stimulation in traumatic brain injury: a phase 1, randomized feasibility study - Schiff, Nicholas D.; Giacino, Joseph T.; Butson, Christopher R.; Choi, Eun Young; Baker, Jonathan L.; O’Sullivan, Kyle P.; Janson, Andrew P.; Bergin, Michael; Bronte-Stewart, Helen M.; Chua, Jason; DeGeorge, Laurel; Dikmen, Sureyya; et al. (Nature medicine, 2023)
Converging evidence indicates that impairments in executive function and information-processing speed limit quality of life and social reentry after moderate-to-severe traumatic brain injury (msTBI). These deficits reflect dysfunction of frontostriatal networks for which the central lateral (CL) nucleus of the thalamus is a critical node. The primary objective of this feasibility study was to test the safety and efficacy of deep brain stimulation within the CL and the associated medial dorsal tegmental (CL/DTTm) tract. Six participants with msTBI, who were between 3 and 18 years post-injury, underwent surgery with electrode placement guided by imaging and subject-specific biophysical modeling to predict activation of the CL/DTTm tract. The primary efficacy measure was improvement in executive control indexed by processing speed on part B of the trail-making test. All six participants were safely implanted. Five participants completed the study and one was withdrawn for protocol non-compliance. Processing speed on part B of the trail-making test improved 15% to 52% from baseline, exceeding the 10% benchmark for improvement in all five cases. CL/DTTm deep brain stimulation can be safely applied and may improve executive control in patients with msTBI who are in the chronic phase of recovery. ClinicalTrials.gov identifier: NCT02881151 . A phase 1 feasibility trial shows that bilateral deep brain stimulation within the central lateral thalamus can be safely applied and is associated with improved executive control.